PERFORMANCE ANALYSIS OF GREEN MANUFACTURING USING GREEN SUPPLY CHAIN OPERATION REFERENCE (GREEN SCOR) AND AHP METHODS AT PT. ABC - Irene Rizda Septiani Aprizal; Rusindiyanto Rusindiyanto (Analit : Analytical and Environmental Chemistry, 2024)
The growth of the manufacturing industry not only has a positive impact on national income but also has a negative impact on environmental issues due to industrial waste from the production process. PT. ABC is a manufacturing company engaged in the production of nuts and bolts. In the production process, there are problems such as a large amount of unprocessed waste and material wastage due to cutting leftovers, which can cause environmental problems. This research aims to determine the value of green manufacturing performance and provide improvement recommendations based on the measurement results for poor indicators so that the company can continue to develop its business well. To measure green manufacturing performance, this research uses the Green SCOR model and the Analytical Hierarchy Process (AHP) weighting method. The calculation results show that the company's final performance value is 67.53, indicating that the company falls into the yellow category, which means it is quite satisfactory. However, four out of twelve KPI indicators studied require improvement. The indicators that need improvement are yield, recyclable waste, waste disposition, and waste produced.